Mac-1 Receptor Clustering Initiates Production of Pro-Inflammatory, Antibacterial Extracellular Vesicles From Neutrophils - Szeifert, Viktória; Kolonics, Ferenc; Bartos, Balázs; Khamari, Delaram; Vági, Pál; Barna, László; Ligeti, Erzsébet; Lőrincz, Ákos M. (Frontiers in Immunology, 2021)
Depending on the prevailing environmental conditions, neutrophilic granulocytes release extracellular vesicles (EV) which have either anti-inflammatory effects on other neutrophils or pro-inflammatory and antibacterial effects. In the present study we investigated the molecular mechanisms underlying the biogenesis of functionally heterogenic EVs. We show that selective stimulation of Mac-1 integrin (complement receptor 3) by specific ligands initiates the generation of EVs which are able to impair bacterial growth and to induce the secretion of the pro-inflammatory cytokine IL-8 (aEV). However, direct Mac-1 stimulation results in aEV release only if neutrophils were activated on ligand coated surfaces whereas soluble ligands are ineffective. Using total internal reflection fluorescence (TIRF) microcopy, an increased clustering of Mac-1 molecules could be visualized in neutrophils added to C3bi coated surfaces; moreover antibody induced cluster formation triggers aEV release as well. Mac-1 induced production of aEV apparently necessitates a strong calcium signal as it fully depends on the presence of extracellular calcium. However, initiation of a strong calcium signal by an ionophore only results the generation of EV devoid of any antibacterial or pro-inflammatory effect. Our results thus demonstrate that stimulation and clustering of Mac-1 is necessary and sufficient for initiation of aEV biogenesis. In contrast, an intracellular calcium signal is necessary but by itself not sufficient for the production of antibacterial and pro-inflammatory EVs.